Doctoral training at the University of Medical Sciences of Cienfuegos using distance learning methods, in the days of COVID-19 - Miriam Iglesias León; Norma Mur Villar; Manuel Cortés Cortés; José Aurelio Diaz Quiñones; Maria Aurelia San Juan Bosch (Medisur)
Foundation: the need to raise health professionals´ scientific potential in the Cienfuegos province is an imperative of the current times. To achieve this purpose, a coordinated, flexible Doctoral Training Strategy is required that can be adapted to the public health context current conditions in times of pandemic. Objective: to describe for the scientific community the results obtained in doctoral training at the University of Medical Sciences of Cienfuegos using distance learning methods for scientific training activities in times of the COVID-19 pandemic. Methods: systematization is used as a research method and the scientific advances of doctoral students are expressed. Results: it was evidenced that distant learning methods used originate a wide range of possibilities in the teaching / learning processes as technological artifacts of scientific production with high communicative and interactive potential. Conclusion: the possibility of maintaining doctoral training in times of pandemic was confirmed.